Public Investment in Renewable Energy R&D under Geopolitical Risks and Economic Uncertainty: A Systematic Review in the Transportation Subsector - N. Heriyah; Putri.Alya; Mesa.Neng (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to examine how public investment in renewable energy research and development (R&D) interacts with geopolitical risks and economic uncertainty, particularly within the transportation subsector, by identifying the extent to which these global factors influence government decisions, fiscal priorities, and technological innovation in renewable energy policy. A systematic literature review (SLR) was conducted following the PRISMA protocol, with data gathered from Scopus, Web of Science, ScienceDirect, Emerald Insight, and IEEE Xplore, focusing on peer-reviewed publications from 2010–2025, where twenty-five qualified studies were synthesized through qualitative content and thematic analysis to extract patterns linking public R&D investment, geopolitical risk, and economic volatility. The review reveals that public investment in renewable energy R&D serves as both a stabilizing and strategic instrument under conditions of global uncertainty, as geopolitical tensions and economic fluctuations initially constrain but ultimately stimulate government-led innovation to enhance energy independence, while technological innovation—particularly in electric mobility, hydrogen fuels, and smart grids—emerges as the key mechanism translating public funding into environmental and socio-economic benefits. Conclusion: Sustained public R&D investment, supported by fiscal capacity, institutional coherence, and policy alignment, is crucial for achieving long-term renewable energy transition in the transportation sector. Limitations: The review is limited to qualitative synthesis and secondary sources, which may reduce generalizability to emerging economies such as Indonesia. Contribution: This study contributes an integrated understanding of how public R&D investment operates as both an economic and strategic policy tool for resilience and sustainability under geopolitical and fiscal uncertainty.